Bacterial healing of geopolymer concrete exposed to combined sulfate and freeze-thaw effects - Ziada, Mahmoud; Tanyildizi, Harun; Uysal, Mucteba (Elsevier Sci Ltd, 2023)
In this study, metakaolin-based colemanite and red mud substituted geopolymer concrete were exposed to combined sulfate and freezing-thawing effects to simulate the effects of cold locations with a sulfate environ-ment. Firstly, samples were exposed to a 5% sodium sulfate solution for four days for combined sulfate and freezing-thawing effects. Then, these samples were subjected to freezing-thawing according to TS EN 15177. Finally, cracks formed on the samples exposed to combined sulfate and freeze-thaw effect. Then, the bacterial healing process was applied to heal the cracks. Sporosarcina pasteurii bacteria were used to form CaCO3 in the cracks. The capillary water absorption, weight measurements, splitting tensile strength, ultrasonic pulse velocity, microstructural analyzes, and visual assessment of bacterial-healed geopolymer concrete samples were per-formed. As a result of this study, the healing ability of Sporosarcina pasteurii was successfully demonstrated by filling cracks caused by the combined durability effect with CaCO3 precipitates. Also, the recovery percentage of splitting tensile strength of the bacterial-healed samples was obtained as 61.71%.
Keywords: Geopolymer concrete; Freeze-Thaw; Sodium Sulfate; Combined durability; Bacterial Healing